2019
DOI: 10.1155/2019/5124026
|View full text |Cite
|
Sign up to set email alerts
|

Kangfuxin Oral Liquid Attenuates Bleomycin-Induced Pulmonary Fibrosis via the TGF-β1/Smad Pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal respiratory disease with a poor prognosis characterized by transforming growth factor (TGF)-β-induced proliferation, migration, and differentiation of fibroblasts, resulting in excessive extracellular matrix (ECM) deposition. Whether Kangfuxin oral liquid (KFXOL) has a protective function in pulmonary fibrosis is largely unknown. The goal of this study was to investigate the potential efficacy of KFXOL, as well as the underlying mechanism by which KFXOL regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In vivo studies further revealed H19 de ciency signi cantly reduced bleomycin-induced pulmonary brosis. TGF-β/smad signaling is one of the key pathways responsible for pulmonary brosis [31,[44][45][46]. The current study indicated that H19 -/mice attenuated the TGF-β/smad signaling in bleomycin damaged lungs by reducing the expression of Tgfb1 mRNA and activated the Smad2/3 protein.…”
Section: Discussionmentioning
confidence: 53%
“…In vivo studies further revealed H19 de ciency signi cantly reduced bleomycin-induced pulmonary brosis. TGF-β/smad signaling is one of the key pathways responsible for pulmonary brosis [31,[44][45][46]. The current study indicated that H19 -/mice attenuated the TGF-β/smad signaling in bleomycin damaged lungs by reducing the expression of Tgfb1 mRNA and activated the Smad2/3 protein.…”
Section: Discussionmentioning
confidence: 53%
“…In vivo studies, we further revealed H19 de ciency signi cantly blocked bleomycin-induced pulmonary brosis and reduced the cell proliferation. TGF-β/smad signaling is one of the key pathways responsible for pulmonary brosis [31,[44][45][46]. We here showed that bleomycin induced Tgfb1 mRNA expression and activated the Smad2 and Smad3, but not in the H19 -/mice.…”
Section: Discussionmentioning
confidence: 56%
“…In vivo studies, we further revealed H19 de ciency signi cantly blocked bleomycin-induced pulmonary brosis and reduced the alveolar type II cells regeneration. TGF-β/smad signaling is one of the key pathways responsible for pulmonary brosis (31,(43)(44)(45). We here showed that bleomycin induced Tgfb1 mRNA expression and activated the Smad1/5, Smad2 and Smad3, but not in the H19-/-mice.…”
Section: Discussionmentioning
confidence: 56%